Beta-spike-containing boosters induce robust and functional antibody responses to SARS-CoV-2 in macaques primed with distinct vaccines - Yixiang Deng; Caroline Atyeo; Dansu Yuan; Taras M. Chicz; Timothy Tibbitts; Matthew Gorman; Sabian Taylor; Valerie Lecouturier; Douglas A. Lauffenburger; Roman M. Chicz; Galit Alter; Ryan P. McNamara (Cell Reports, 2023)
Summary: The reduced effectiveness of COVID-19 vaccines due to the emergence of variants of concern (VOCs) necessitated the use of vaccine boosters to bolster protection against disease. However, it remains unclear how boosting expands protective breadth when primary vaccine platforms are distinct and how boosters containing VOC spike(s) broaden humoral responses. Here, we report that boosters composed of recombinant spike antigens of ancestral (prototype) and Beta VOCs elicit a robust, pan-VOC, and multi-functional humoral response in non-human primates largely independent of the primary vaccine series platform. Interestingly, Beta-spike-containing boosters stimulate immunoglobulin A (IgA) with a greater breadth of recognition in protein-primed recipients when administered with adjuvant system 03 (AS03). Our results highlight the utility of a component-based booster strategy for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for broad humoral recognition, independent of primary vaccine series. This is of high global health importance given the heterogeneity of primary vaccination platforms distributed.